Analisis Implementasi SAK ETAP Pada Laporan Keuangan Badan Usaha Milik Desa: Studi Kasus Pada BUMDes Di Desa Tuban - Adi Supeno (Jurnal Kendali Akuntansi, 2023)
This study aims to determine the application of SAK ETAP in the preparation of BUMDes financial statements in Tuban The data analysis technique in this study is a qualitative descriptive method and only describes the results of interviews and documentation conducted in the field. There were 14 BUMDes analyzed. The results of this study indicate that there are only 13 BUMDes that have financial statements with the advantages and disadvantages of each New Usaha BUMDes, Rato New Business BUMDes, Sama Kai BUMDes, Soro Mandiri BUMDes and Harapan Bersama BUMDes only make a balance sheet. BUMDes Maja Labo Dahu and BUMDes Lu’u Lambu only make profit and loss statements. BUMDes Mantika Lanta only makes reports on changes in capital, BUMDes Damai only makes profit and loss reports and balance sheets. BUMDes Meci Angi. BUMDes Melayu Mekar, BUMDes Mangge Baru and BUMDes Hidi Rasa only make general cash books in the form of cash in and cash out. Meanwhile, according to SAK ETAP, there are five types of financial statements that must be made, namely balance sheets and income statements. Loss, statement of changes in equity, statement of cash flows and notes to financial statements.